OPTIMALISASI KEBUTUHAN TENAGA KERJA, BERDASARKAN ANALISIS BEBAN KERJADI PT. NICEPRO MEGATAMA - Widya, Lestari; Oka, Martini (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT PT. Nicepro Megatama is a company that have business on produce of product or raw material food become serve food, fluency of production process at this company effected by determination of appropriate employee number. This study aim to find out the optimaiitzation of employee need based on work load analysis at PT. Nicepro Megatama. This study is descriptive. Data collecting method by using interview, documentation and observation. Data analysis technique was conducted by qualitative descriptive method. Planning of employee and employee need at PT. Nicepro Megatama based on the work laod can be concluded that in 2014 mean of employee will be need for each month is                      35 people to produce meat by mean of 2.078 kg. while number of employee that has been exist at PT. Nicepro Megatama in 2014 by mean is 42 people. Thus it compare that mean of employee in 2014 with mean of employee total that should be exist, hence in 2014 has been occurred over labour at each month as much of 7 people.